(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the pedagogical requirements, criteria, software and stages for improving the mechanism of independent learning of students with the help of information technologies from today’s point of view. Social, psychological, pedagogical, methodical literature on independent education based on information technologies are presented. Pedagogical requirements, criteria, software, forms and stages of creation are described as a whole integrated system through scientific theoretical research and analysis, as well as pedagogical requirements and criteria for information technology Reforms in the education system are discussed from the point of view of modern information technologies.